Is it possible to make environmental science relevant to society at-large? - Adam Rosenblatt (Ideas in Ecology and Evolution, 2017)
Over the last five U.S. presidential election cycles, public concern about environmental issues has seemingly declined while concerns about national security and economic issues have remained steady or increased. These changes in public attitudes have been associated with decreased attention to environmental issues amongst policymakers, a situation that contrasts strongly with the 1970s when public concern about environmental issues was high and environmental legislation was a U.S. federal government priority. “Framing” has been proposed as a tool that environmental scientists could use to increase the relevancy of their research to U.S. society at-large, thereby helping to change public attitudes and influence policymaking. However, if done haphazardly, some framing efforts can actually have the opposite effect. To combat this weakness, environmental scientists should join with experts in psychology, decision science, and social science to create interdisciplinary teams that can effectively communicate with the public, positively affect public opinion, and make environmental science more relevant and meaningful to society at-large.